Modern Tragedy - Williams Raymond (The Hogarth Press, 1992)
A classic work of cultural criticism, Modern Tragedy is a study of the dramatic form in the twentieth century. Acknowledgements, Foreword, Tragic Ideas, Tragedy and Experience, Tragedy and the Tradition, Tragedy and Contemporary Ideas, Tragedy and Revolution, Continuity, Modern Tragic Literature, From Hero to Victim, Private Tragedy, Social and Personal Tragedy, Tragic Deadlock and Stalemate, Tragic Resignation and Sacrifice, Tragic Despair and Revolt, A Rejection of Tragedy, Koba, Index.